Pembelajaran Sejarah Daring Menggunakan Media Power Point Bersuara - Anita Novianti; Iing Yulianti (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2022)
Since the outbreak of Covid-19, teachers were asked to organize creative and innovative online learning to support the continuity of the learning process. In online history learning, teachers can use voice-over power point as learning media. This study aims to obtain a description of the online history learning using voice-over power point in SMA Negeri 1 Cisarua. The method used in this research is a study of qualitative descriptive. The results of this study indicate that there are several things that the teacher prepares before carrying out the online history learning such as compiling the RPP and designing voice-over power point. The online history learning using voice power point media is carried out through google classroom. The teacher utilises voice-over power point as a media to deliver lesson material to students. However, there are a few deficiencies in this learning such as lack of direct interaction between students and teachers, and lack of student involvement in the learning process. Nevertheless, in general students gave positive responses regarding online history learning using voice power point media.